2014
DOI: 10.1111/jcmm.12345
|View full text |Cite
|
Sign up to set email alerts
|

HDAC‐inhibitor (S)‐8 disrupts HDAC6‐PP1 complex prompting A375 melanoma cell growth arrest and apoptosis

Abstract: Histone deacetylase inhibitors (HDACi) are agents capable of inducing growth arrest and apoptosis in different tumour cell types. Previously, we reported a series of novel HDACi obtained by hybridizing SAHA or oxamflatin with 1,4-benzodiazepines. Some of these hybrids proved effective against haematological and solid cancer cells and, above all, compound (S)-8 has emerged for its activities in various biological systems. Here, we describe the effectiveness of (S)-8 against highly metastatic human A375 melanoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Furthermore, PTB knockdown improved the phosphorylation of Akt (Figure 5E). Among all the proteins whose mRNA has been identified to physically interact with PTBP3 (Brazão et al , 2012), HDAC6 has been reported to be a regulator of p-Akt level (Balliu et al , 2015). We thus tested whether HDAC6 mediated PTBP3 inhibition-induced cell chemosensitisation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, PTB knockdown improved the phosphorylation of Akt (Figure 5E). Among all the proteins whose mRNA has been identified to physically interact with PTBP3 (Brazão et al , 2012), HDAC6 has been reported to be a regulator of p-Akt level (Balliu et al , 2015). We thus tested whether HDAC6 mediated PTBP3 inhibition-induced cell chemosensitisation.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, HDAC6 has been reported to form a complex with protein phosphatase 1 (PP1). Disruption of HDAC6/PP1 complex released active PP1 which could dephosphorylate Akt (Balliu et al , 2015). Inhibition of Akt was found to decrease the expression of TYMS (Ahn et al , 2015), critical determinant of 5-FU sensitivity in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in HDAC activity alters expression of MHC (Major histocompatibility complex) and costimulatory molecules [ 118 , 119 ]. The subsequent increase in immunogenicity intensifies activation of T cells and the prolonged survival of experimental animals [ 120 , 121 ].…”
Section: Mechanisms Of Hdac Inhibitors Actionmentioning
confidence: 99%
“…HDAC6 is a unique histone deacetylase harboring two active N-terminal deacetylating domains and a C-terminal ubiquitin-binding domain [26,27]. HDAC6, which is primarily expressed in the cytoplasm, clears the acetyl group from lysine residues in a number of non-histone substrates, including α-tubulin, stress granules and HSP90 [14,28,29]. Aberrant expression of HDAC6 is involved in several physiological processes such as stress response (ER stress), apoptosis and autophagy that play crucial roles in tumors, neurodegenerative disorders, inflammation and kidney diseases [15,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple cellular functions, including cell apoptosis, were modulated by the acetylation of histone and non-histone proteins. An acetylation could be added to a lysine residue by histone acetyl transferases and be cleaved by histone deacetylases (HDACs) [14]. HDACs were classified based on their structure and homology: class I (HDAC1, 2, 3 and 8); class II (HDAC4, 5, 6, 7, 9 and 10); class III (SIRT1-7); and class IV (HDAC11) [15].…”
Section: Introductionmentioning
confidence: 99%